The effect of tranexamic acid-loaded alginate scaffolds on bone formation: hemostatic and histomorphometric analysis in a rabbit model - Mai El Halawany; Heba Ahmed Saleh; Mohammed Khashaba; Mohamed H. H. AbouGhaly; Randa Latif (Future Journal of Pharmaceutical Sciences)
Abstract Background Bone tissue regeneration based on the use of porous biomaterial scaffolds is considered a promising approach for treating bone defects and fractures healing. A porous alginate scaffold comprising hydroxyapatite nanoparticles loaded with tranexamic acid was formulated. The prepared scaffolds were characterized in terms of the release profile of tranexamic acid and scanning electron microscopy imaging. A cranial bone defect in rabbits (6 defects/3 rabbits/group) was used as a model for the assessment of hemostatic activity of the used scaffolds and the assessment of the bone formation histomorphometrically after its application for 14 days. Results The scaffold appeared with irregular porous structure and controlled the release of tranexamic acid over 4 h. The hemostatic time of the medicated and non-medicated scaffolds were 20 and 60 s, respectively. They were significantly lower than the control group (200 s, p < 0.05). The microscopic examination was done after staining histologically prepared sections from the bone defect with Masson trichrome stain and the area % of the newly developed bone was computed. For the medicated group, the new bone area % (75.8 ± 4.9%) was significantly higher than the non-medicated group (58.1 ± 5.9%, p < 0.001). Both groups were significantly larger than the control group that showed bone area % of 43.1 ± 5.6 (p < 0.05). The histomorphometric analysis showed that the medicated scaffold-treated group had more mineralized newly formed bone tissue and smaller amount of soft tissue and residual materials. In contrast, the non-medicated scaffold showed non-mineralized bone cells with larger soft tissue and residual materials. Conclusion These results suggested the promising effect of the tranexamic acid-loaded scaffolds in minimizing the time to reach hemostasis by stabilization of the formed hematoma. Additionally, they could improve the quality (mineralization) and the quantity (amount) of the newly formed bone. Graphical abstract